Impacts of GlobalConsent, a Web-Based Social Norms Edutainment Program, on Sexually Violent Behavior and Bystander Behavior Among University Men in Vietnam: Randomized Controlled Trial - Kathryn M Yount; Yuk Fai Cheong; Irina Bergenfeld; Quach Thu Trang; Jessica M Sales; Yiman Li; Tran Hung Minh (JMIR Publications, 2023)
BackgroundSexual violence against women is prevalent worldwide. Prevention programs that treat men as allies and integrate a bystander framework are emerging in lower income settings, but evidence of their effectiveness is conflicting. ObjectiveThis study aimed to test the impact of GlobalConsent on sexually violent behavior and prosocial bystander behavior among university men in Vietnam. MethodsWe used a double-blind, parallel intervention versus control group design with 1:1 randomization at 2 universities. A total of 793 consenting heterosexual or bisexual men aged 18-24 years who matriculated in September 2019 were enrolled and assigned randomly to GlobalConsent or an attention-control adolescent health education (AHEAD) program. GlobalConsent is an adapted, theory-based, 6-module web-based intervention with diverse behavior change techniques and a locally produced serial drama. AHEAD is a customized, 6-module attention-control program on adolescent health. Both the programs were delivered to computers and smartphones over 12 weeks. Self-reported sexually violent behaviors toward women in the prior 6 months and prosocial bystander behaviors in the prior year were measured at 0, 6, and 12 months. ResultsMore than 92.7% (735/793) of men in both study arms completed at least 1 program module, and >90.2% (715/793) of men completed all 6 modules. At baseline, a notable percentage of men reported any sexually violent behavior (GlobalConsent: 123/396, 31.1%; AHEAD: 103/397, 25.9%) in the prior 6 months. Among men receiving GlobalConsent, the odds of reporting a high level (at least 2 acts) of sexually violent behavior at the endline were 1.3 times the odds at baseline. Among men receiving AHEAD, the corresponding odds ratio was higher at 2.7. The odds of reporting any bystander behavior at endline were 0.7 times the odds at baseline for GlobalConsent, and the corresponding odds ratio for AHEAD was lower at 0.5. ConclusionsCompared with a health attention-control condition, GlobalConsent has sustained favorable impacts on sexually violent behavior and prosocial bystander behavior among matriculating university men in Vietnam, who would otherwise face increasing risks of sexually violent behavior. GlobalConsent shows promise for national scale-up and regional adaptations. Trial RegistrationClinicalTrials.gov NCT04147455; https://clinicaltrials.gov/ct2/show/NCT04147455 International Registered Report Identifier (IRRID)RR2-10.1186/s12889-020-09454-2